Freshwater challenges of South Africa and its upper Vaal River : current state and outlook - Du Plessis, Anja (Springer, 2017)
"This book promotes better understanding and awareness of South Africa' significant water problems by describing the country's and especially the Upper Vaal River?s water resources. It is a "go-to" book for students, professionals and regular citizens when information is required regarding the country's and more specifically the Upper Vaal River?s freshwater resources. It highlights the major problems and risks which need to be addressed and give a realistic and true representation of the current water affairs."
Keywords: Water-supply -- South Africa.; Fresh water -- South Africa.; South Africa.; elektronické knihy; electronic books